Do the Colors of Educational Number Tools Improve Children's Mathematics and Numerosity?. Issue 4 (3rd October 2019) - Rinaldi, Louisa J.; Smees, Rebecca; Alvarez, James; Simner, Julia
Abstract : This study examined how colored educational tools improve children's numerosity ("number sense") and/or mathematics. We tested children 6–10 years ( n  = 3, 236) who had been exposed to colored numbers from the educational tools Numicon (Oxford University Press, 2018) or Numberjacks (Ellis, 2006), which map colors to magnitudes or Arabic numerals, respectively. In a free association task pairing numbers with colors, a subset of children spontaneously provided colors matching one of these schemas. These children, who had internalized Numicon (colored magnitude), showed significantly better numerosity but not mathematics compared to peers. There was no similar benefit from internalizing Numberjacks (colored numerals). These data support a model in which colored number tools provide benefits at different levels of numerical cognition, according to their different levels of cross‐modal mappings.